2018
DOI: 10.22158/wjer.v5n1p52
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Challenges and Coping Mechanisms in Educating Learners with Disabilities among Some Selected Special Needs Units in Mombasa County, Kenya

Abstract: Inclusion of children with disability in the special units has been a great challenge in many counties in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The results indicated that VSM strategy as a useful tool to help struggling readers. Maguire (2015) study in New Zealand indicated that daily reading diary scores did not provide enough information to determine if video modeling affect reading attitudes. The findings did not find a positive relationship between increased attitude and watching of video.…”
Section: Introductionmentioning
confidence: 98%
“…The results indicated that VSM strategy as a useful tool to help struggling readers. Maguire (2015) study in New Zealand indicated that daily reading diary scores did not provide enough information to determine if video modeling affect reading attitudes. The findings did not find a positive relationship between increased attitude and watching of video.…”
Section: Introductionmentioning
confidence: 98%
“…The results indicated that VSM strategy as a useful tool to help struggling readers. Maguire (2015) study in New Zealand indicated that daily reading diary scores did not provide enough information to determine if video modeling affect reading attitudes. The findings did not find a positive relationship between increased attitude and watching of video.…”
Section: Introductionmentioning
confidence: 98%